Microexplosion of Three-Phase Diesel-Methanol-Water Emulsion Spray - Wu, Dongyin; Wang, Wuqiang; Sheng, Hongzhi; Yao, Ji (Asian Journal of Chemistry, 2012)
The development processes of the diesel-methanol-water emulsion sprays have been observed by a high-speed CCD camera at different temperatures and pressures. It is found that in the range of this experiment, the higher the ambient pressure the more beneficial to the occurrence of microexplosion. In the range of adequate temperatures, there is greater intensity of microexplosion. If the temperature is too high or too low, the microexplosion is very difficult to take place. At the same time, the delay of the microexplosion will decrease with the increasing ambient temperature. In this paper, using the high-speed CCD photography technology, we have verified that at an appropriate temperature and pressure, the microexplosion will inevitably take place in the three-phase diesel-methanol-water emulsion sprays. At different places all around the emulsion sprays, group microexplosions can be observed repeatedly. The microexplosion is able to greatly expand the spraying area.